Interplay of primary sequence, position and secondary RNA structure determines alternative splicing of LMNA in a pre-mature aging syndrome. Issue 11 (22nd April 2019) - Shilo, Asaf; Tosto, Frances Anne; Rausch, Jason W; Le Grice, Stuart F J; Misteli, Tom
Abstract: Aberrant splicing in exon 11 of the LMNA gene causes the premature aging disorder Hutchinson-Gilford Progeria Syndrome. A de novo C1824T mutation activates an internal alternative 5′ splice site, resulting in formation of the disease-causing progerin protein. The underlying mechanism for this 5′ splice site selection is unknown. Here, we have applied a combination of targeted mutational analysis in a cell-based system and structural mapping by SHAPE-MaP to comprehensively probe the contributions of primary sequence, secondary RNA structure and linear splice site position in determining in vivo mechanisms of splice site choice in LMNA . While splice site choice is in part defined by sequence complementarity to U1 snRNA, we identify RNA secondary structural elements near the alternative 5′ splice sites and show that splice site choice is significantly influenced by the structural context of the available splice sites. Furthermore, relative positioning of the competing sites within the primary sequence of the pre-mRNA is a predictor of 5′ splice site usage, with the distal position favored over the proximal, regardless of sequence composition. Together, these results demonstrate that 5′ splice site selection in LMNA is determined by an intricate interplay among RNA sequence, secondary structure and splice site position.